A comparative study in aggression between adolescent boys and girls of tribal and non-tribal students in Chitagong Hill Tracts - Ahmed, Rasel; Haque, M Enanul (Journal of Life and Earth Science, 2011)
The present study was an effort to conduct an empirical investigation behaviour on aggression in adolescent boys and girls of tribal (i.e. Chakma) and non-tribal (i.e. Bengali) students in Chittagong Hill Tracts. A sample consisting of 360 respondents was selected from tribal (N = 160) and non-tribal (N = 160) subjects. Each group was equally divided into boys and girls. Each gender was then equally divided into early and late adolescents. Thus, the study used a 2×2×2 factorial design representing two races (Chakma/Bengali), two genders (boys/girls) and two stages of development (early adolescence/late adolescence). The Measure of Aggressive Behaviour (MAB) was administered on the sample for data collection. Regardless of gender and stage of development, tribal respondents were found to express significantly higher rates of aggression than non-tribal respondents. Again, regardless of race and stage of development, boys expressed significantly higher rates of aggression than girls. Similarly, regardless of race and gender, respondents at early adolescent stage expressed significantly higher rates of aggression than the respondents at late adolescent stage. Key words: Aggression; adolescence; race; sex; stages of development DOI: 10.3329/jles.v2i2.7502 J. Life Earth Sci., Vol. 2(2) 79-84, 2007